Expert System To Diagnose Pregnancy Diseases In Women Using Naive Bayes Method - Dini Syahfitri; Serasi Ginting, Budi; Sihombing, Anton (Ali Institute or Research and Publication, 2022)
Expert system is a system that uses human knowledge, where the knowledge is entered into a computer, and then used to solve problems that usually require human expertise or expertise. In this case the expert system is used to diagnose pregnancy diseases in women. Pregnancy disease is a condition in which there is a disturbance in pregnancy or the fetus in the womb. An expert system for diagnosing pregnancy diseases in women is an expert system designed as a tool for diagnosing types of pregnancy diseases. Computer programs are intended to provide aids in solving problems in certain areas of specialization such as pregnancy problems in women. This knowledge is obtained from various sources including books and the internet related to the causes of pregnancy in women. The knowledge base is structured in such a way as to become a database with several disease tables and symptom tables to facilitate system performance in drawing conclusions on this expert system using Naive Bayes. This expert system will display a choice of symptoms that can be selected by the user, where each symptom choice will read the user to the next symptom choice to get the final result.